Results of the count of juvenile pink salmon Oncorhynchus gorbuscha in the Malaya Khuzi River (Sakhalin Island) in 2022–2024 - A. N. Elnikov; A. A. Zhivoglyadov; О. V. Zelennikov (Известия ТИНРО)
Migration of juvenile pink salmon Oncorhynсhus gorbuscha in the Malaya Khuzi River (northeastern Sakhalin Island) was studied in May-July of 2022, 2023 and 2024. In these three years, they migrated downstream in different timing and in different number. In 2022, only 468 ind./min. on average migrated in the period of mass migration on June 12–18 with a peak on June 15. In 2023, the average number of counted fry was significantly higher — 3545 ind./min., and the mass migration occurred earlier — on June 6–10 with a peak on June 8. In 2024, on average 9467 ind./min. were counted in the extended period of mass migration from May 26 to June 7 with a peak on June 1. In 2023 and 2024, dense sea ice was observed near the seashore and water temperature in the coastal area was about 0 °C during the mass migration of juveniles. Spatial distribution of commercial pink salmon catches along the southern part of the northeastern Sakhalin coast is analyzed and it is concluded that their downstream migration in the Malaya Khuzi River is not representative for the entire area, at least for the year-class of 2022 migrated in 2023.